2015
DOI: 10.1038/srep10305
|View full text |Cite
|
Sign up to set email alerts
|

A systems-biological study on the identification of safe and effective molecular targets for the reduction of ultraviolet B-induced skin pigmentation

Abstract: Melanogenesis is the process of melanin synthesis through keratinocytes-melanocytes interaction, which is triggered by the damaging effect of ultraviolet-B (UVB) rays. It is known that melanogenesis influences diverse cellular responses, including cell survival and apoptosis, via complex mechanisms of feedback and crosstalk. Therefore, an attempt to suppress melanin production by modulating the melanogenesis pathway may induce perturbations in the apoptotic balance of the cells in response to UVB irradiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…UVB is radiation at 280–320 nm, in the natural ultraviolet band of the spectrum and is associated with skin conditions such as sunburn and photocarcinogenesis 48 67 68 . Many studies have reported that various natural agents (e.g., epigallocatechin gallate 69 , pomegranate polyphenol extract 70 , and resveratrol 36 ) have photoprotective effects against UV injury.…”
Section: Discussionmentioning
confidence: 99%
“…UVB is radiation at 280–320 nm, in the natural ultraviolet band of the spectrum and is associated with skin conditions such as sunburn and photocarcinogenesis 48 67 68 . Many studies have reported that various natural agents (e.g., epigallocatechin gallate 69 , pomegranate polyphenol extract 70 , and resveratrol 36 ) have photoprotective effects against UV injury.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the biological properties of the human signaling network, we analyzed the input–output relationship of the network [ 19 , 21 ]. In the Boolean simulation, the states of all nodes in the network were updated according to their assigned logical rules at each simulation step.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the transition in the cellular state of the human signaling network during colorectal tumorigenesis, we performed the attractor landscape analysis of the human signaling network [ 10 , 21 , 22 ]. The attractor landscape is composed of attractors and their basins of attraction where an attractor is one of the steady-states of the network and the basin of an attractor represents a set of network states that converge to the attractor.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it was found that β-catenin functionally interacts with the MITF protein itself and inhibition of β-catenin can effectively reduce the melanin production. 27 Relatively small sample size was the main limitation of the current work. Therefore, we recommend further large-scaled studies to validate our findings as this is the first study that evaluates…”
Section: Discussionmentioning
confidence: 97%